First metatarsophalangeal arthroscopy in patients with post-traumatic hallux valgus. Issue 4 (December 2015) - Lui, T.H.
Highlights: Post-traumatic hallux valgus after medial collateral ligament injury has a high incidence of MTP-1 pathology. Post-traumatic hallux valgus can present as MTP-1 joint pain. First MTP arthroscopy has both diagnostic and therapeutic values in management of joint pain in post-traumatic hallux valgus. Abstract: Post-traumatic hallux valgus is relatively rare and has been reported after rupture of the medial collateral ligament of the ﬁrst metatarsophalangeal (MTP-1) joint; Lisfranc joint injury; turf toe injury; medial plantar nerve entrapment secondary to tibial fracture or first metatarsal fracture. Post-traumatic hallux valgus after medial collateral ligament injury has a high incidence of MTP-1 pathology. Detailed history and clinical examination can facilitate differentiation of the source(s) of the patient's symptoms and assist accurate formulation of the surgical plan. First, MTP arthroscopy is a feasible diagnostic and therapeutic tool to manage the MTP-1 joint pain in hallux valgus following injury to the MTP-1 joint.